Overexpression of OSM and IL-6 impacts the polarization of pro-fibrotic macrophages and the development of bleomycin-induced lung fibrosis. Issue 1 (December 2017) - Ayaub, Ehab; Dubey, Anisha; Imani, Jewel; Botelho, Fernando; Kolb, Martin; Richards, Carl; Ask, Kjetil
Abstract Although recent evidence indicates that gp130 cytokines, Oncostatin M (OSM) and IL-6 are involved in alternative programming of macrophages, their role in lung fibrogenesis is poorly understood. Here, we investigated the effect of transient adenoviral overexpression of OSM or IL-6 in mice during bleomycin-induced lung fibrosis. Lung fibrosis and M2-like macrophage accumulation were assessed by immunohistochemistry, western blotting, gene expression and flow cytometry.Ex-vivo isolated alveolar and bone marrow-derived macrophages were examined for M2-like programming and signalling. Airway physiology measurements at day 21 demonstrated that overexpression of OSM or IL-6 exacerbated bleomycin-induced lung elastance, consistent with histopathological assessment of extracellular matrix and myofibroblast accumulation. Flow cytometry analysis at day 7 showed increased numbers of M2-like macrophages in lungs of mice exposed to bleomycin and OSM or IL-6. These macrophages expressed the IL-6Rα, but were deficient for OSMRβ, suggesting that IL-6, but not OSM, may directly induce alternative macrophage activation. In conclusion, the gp130 cytokines IL-6 and OSM contribute to the accumulation of profibrotic macrophages and enhancement of bleomycin-induced lung fibrosis. This study suggests that therapeutic strategies targeting these cytokines or their receptors may be beneficial to prevent the accumulation of M2-like macrophages and the progression of fibrotic lung disease.